Karakteristik Morfologi Ikan Nila (Oreochromis niloticus) Pada Pengelolaan Budidaya Ikan Di Kampung Buah Jakung Kabupaten Serang - Tri Asih Handayani; Wanda Sofi Nurfitriniha; Ani Fuziyanti; Vina Rizkika; Ima Ismayati (Universitas Nusantara PGRI Kediri, 2024)
Tilapia (Oreochromis niloticus), also known as tilapia or tilapia, is one of the economically important freshwater fish that was introduced to some parts of Asia, including Indonesia. Morphological features include morphometric and meristic studies of fish. Morphometrics are characteristics related to body size while meristic measurements are part of the standard measurements used in fish. The method used in this study is a qualitative method, aiming to determine the morphological characteristics of tilapia. Observations were made based on total length (Tl), head length (HL), standard length (SL), head height, fork length (FL), body height, interorbital distance, eye diameter, mouth opening width, dorsal height, maxillary length, length mandible, operculum length, prepectoral length, predorsal length.